Building brand reputation of the fast food industry through customer’s satisfaction in the United Arab Emirates - Alkaabi, Mohammed Rashed Abdulla Zuhair (2023)
Making brand reputation is becoming an important element to gain long-term profitability and competitive advantage. This study has choosed the Abu Dhabi fast food restaurants as the target industry to investigate and a few variables was chosen which are price, service quality, food quality, physical environment and analyzed the factors of customer satisfaction of Abu Dhabi in McDonald's fast food industry. Customers satisfaction can be described as the feelings of happiness, pleasure, relief, acceptance, anddelight. Thus, it is necessary to analyze how the four dimensions can affect customer satisfaction in fast food industry. In marketing, brand reputation is defined as a consumer’s commitment to repeat purchase, it also endorses the trust towards the brand and it also shows the quality and performance of products. The McDonald's fast food industry is being adopted to UAE food requirements and is a growing phenomenon in UAE, and it is significant for McDonald's fast food restau-rants’ owner to clearly understand which dimensions enable to stand out among other com-petitors and increase customer satisfaction and brand reputation. The main objective of this research is to investigate the factors influencing customer satisfaction and brand reputation of McDonald's restaurants in the United Arab Emirates (Abu Dhabi). Data for this study were collected from a sample of 421 respondents who has visited the McDonald's fast food restaurant in Abu Dhabi and had the dining experience in McDonald's fast food restaurant. The collected data was analyzed using Statistical Package for Social Science (SPSS) version 22.0 and Partial Least Squares (PLSSEM) with SmartPLS version 3. The multicollinearity test is one of the preliminary analysis, and this test is used in the study to ensure that all the items of the independent variable and the mediator variable are correlated to each other. The variance inflation factors (VIF) is used to measure the multicollinearity. The findings illus-trated that service quality and physical environment factors have positive influence on cus-tomer satisfaction while price and food quality do not have a significant impact. Hence, it is recommended to the fast food managers especially McDonald's restaurants to appropriately follow specific tactics to improve those components and customer satisfaction and brand reputation.